Ecoprint-Preneurship : Strategies for Local Economic Development and Sustainable Tourism Through Ecoprint Training - Rahmaningtyas, Wisudani; Widhiastuti, Ratieh; Purasani, Hana Netti; Apriliana, Shalum Rizki (Jurnal Pengabdian UNDIKMA, 2024)
This service program aims to educate the community about the ecoprint method, an environmentally friendly printing technique that uses natural materials, such as local plant leaves, to create value-added products. The service method Â includes counseling, skill development, as well as lectures, practice, mentoring, monitoring, and evaluation. The data analysis used is descriptive analysis. The results of this service activity are increased community knowledge and skills in optimally utilizing natural potential and supporting sustainable economic development in Nyatnyono Village. Evaluation results showed high satisfaction with the relevance of the material, clarity of presentation, team responsiveness, and resource availability, although areas for improvement included language clarity, presentation structure, and ensuring adequate time for skill mastery. Overall, the community service activity had a significant positive impact on enhancing technical skills and creating new economic opportunities for the community.